EFEKTIVITAS PENYALURAN DANA BANTUAN SOSIAL TUNAI PADA MASA PANDEMI COVID-19 DI KABUPATEN ROKAN HILIR - Siti Nurhafika; Dedi Kusuma Habibie (Jurnal Sumber Daya Manusia Unggul (JSDMU), 2022)
The spread of Covid-19 throughout the world has caused many impacts, one of which is on the global economy in 2020, as a result many people are unable to meet their daily needs. Therefore, the government is quick to make various innovative programs to help people affected by Covid-19. One of them is the government making the Cash Social Assistance Program (BST) provided by the Ministry of Social Affairs. The purpose of this study is to describe the effectiveness of the distribution of Cash Social Assistance funds during the Covid-19 Pandemic in Rokan Hilir Regency and to analyze the inhibiting factors for the distribution of Cash Social Assistance (BST). The theory used in this research is Budiani's theory which has four indicators, namely targeting accuracy, program socialization, program objectives, and program monitoring. The research method used is qualitative research with a descriptive approach. In this research, the writer collects data by using observation, interview and documentation techniques. The results showed that the effectiveness of the distribution of cash social assistance funds during the Covid-19 pandemic in Rokan Hilir Regency was described in four indicators, that the obstacle for this study was data validation and funds were not disbursed because there were many invalid Niks.